Optimizing Shade Cultivation Method and Irrigation Amount to Improve Photosynthetic Characteristics, Bean Yield, and Quality of Coffee in a Subtropical Monsoon Climate - Hao, Kun; Liu, Xiaogang; Wang, Xiukang; Fei, Liangjun; Liu, Lihua; Jie, Feilong; Li, Yilin; Yang, Qiliang; Shan, Yunhui (Frontiers in Plant Science, 2022)
Reasonable water and light management technology can improve economic benefits, coffee yield, and quality. We used cluster analysis and principal component analysis to evaluate and optimize the water and light management technology with high coffee yield, quality, and economic benefits in a subtropical monsoon climate region of China. The experiment was arranged in a randomized complete block design with two factors (3 irrigation levels × 4 shade cultivation treatments) replicated four times during 2016–2017. The irrigation levels consisted of full irrigation (FI) and two deficit irrigations (DIL: 75% FI, DIS: 50% FI). The shade cultivation treatments consisted of no shade cultivation (S0) and three shade cultivation modes (SL: intercropping with four lines of coffee and one line of banana; SM: intercropping with three lines of coffee and one line of banana; SS: intercropping with two lines of coffee and one line of banana). The results showed that the effects of irrigation level and shade cultivation mode on growth, crop yield, most of the photosynthetic characteristics, and nutritional quality were significant (p < 0.05). Regression analysis showed that the leaf radiation use efficiency (RUE) showed a significant negative exponential relation or logistic-curve variation with photosynthetically active radiation (PAR). The bean yield increased with an increase of the shade degree when water was seriously deficient, whereas it first increased and then decreased with an increase of the shade degree under FI and DIL. Based on both cluster analysis and principal component analysis, the FISS treatment resulted in the highest comprehensive quality of coffee, followed by the FISM treatment; the DISS0 treatment obtained the lowest quality. Compared with the FIS0 treatment, the FISM treatment increased the 2-year average bean yield and net income by 15.0 and 28.5%, respectively, whereas the FISS treatment decreased these by 17.8 and 8.7%, respectively. To summarize, FISS treatment significantly improved the nutritional quality of coffee, and FISM treatment significantly increased the dry bean yield and economic benefits of coffee. The results of the study could provide a theoretical basis for water-saving irrigation and shade cultivation management of coffee in a subtropical monsoon climate region of China.